Caesar source finder: Recent developments and testing. (2019) - Riggi, S.; Vitello, F.; Becciani, U.; Buemi, C.; Bufano, F.; Calanducci, A.; Cavallaro, F.; Costa, A.; Ingallinera, A.; Leto, P.; Loru, S.; Norris, R. P.; et al.
Abstract: A new era in radio astronomy will begin with the upcoming large-scale surveys planned at the Australian Square Kilometre Array Pathfinder (ASKAP). ASKAP started its Early Science programme in October 2017 and several target fields were observed during the array commissioning phase. The Scorpio field was the first observed in the Galactic Plane in Band 1 (792–1 032 MHz) using 15 commissioned antennas. The achieved sensitivity and large field of view already allow to discover new sources and survey thousands of existing ones with improved precision with respect to previous surveys. Data analysis is currently ongoing to deliver the first source catalogue. Given the increased scale of the data, source extraction and characterisation, even in this Early Science phase, have to be carried out in a mostly automated way. This process presents significant challenges due to the presence of extended objects and diffuse emission close to the Galactic Plane. In this context, we have extended and optimised a novel source finding tool, named Caesar, to allow extraction of both compact and extended sources from radio maps. A number of developments have been done driven by the analysis of the Scorpio map and in view of the future ASKAP Galactic Plane survey. The main goals are the improvement of algorithm performances and scalability as well as of software maintainability and usability within the radio community. In this paper, we present the current status of Caesar and report a first systematic characterisation of its performance for both compact and extended sources using simulated maps. Future prospects are discussed in the light of the obtained results.